Structural basis for the allosteric regulation and catalytic mechanism of Staphylococcus aureus UMP kinase - Gao, Yan; Zhu, Zhongliang; Wang, Lianyu; Ke, Jiyuan; Niu, Liwen (Frontiers in Microbiology, 2026)
Staphylococcus aureus uridine monophosphate kinase (saUMPK) functions as a hexameric enzyme that catalyzes the reversible reaction: Mg2+ ⋅ ATP + UMP ↔ Mg2+ ⋅ ADP + UDP. As a key enzyme in pyrimidine metabolism with no detectable homologs in eukaryotes, saUMPK represents an attractive antibacterial target. In this study, we determined crystal structures of saUMPK in complex with various nucleotides, including UMP (3.26 Å), UDP (2.75 Å), GTP (2.88 Å), UTP (2.30 Å), ATP/GTP (2.88 Å), and ATP/UMP (2.57 Å), and performed complementary biochemical assays. Structurally, our analyses revealed several key findings: (1) We captured a previously unobserved apo-like conformation of saUMPK; (2) We identified key residues involved in UMP recognition and revealed the substrate-binding plasticity at the ATP donor site; (3) We uncovered that the allosteric site accommodates different nucleotides through a conserved network of basic residues (R101, R119, R122, K126, and R128). Notably, both the type and number of bound nucleotides cooperatively regulate the final conformational state of the saUMPK hexamer. GTP molecules fully occupy the allosteric sites, stabilizing the open conformation and preserving the global threefold symmetry. In contrast, UTP, ATP, or UDP only partially occupy the allosteric sites, resulting in a loss of this symmetry, while ATP or UDP binding further induces a U-shaped closed conformation of the hexamer. Site-directed mutagenesis identified key residues critical for enzymatic activity. These insights provide a foundation for designing broad-spectrum inhibitors targeting UMP kinase from Staphylococcus aureus and related Gram-positive bacteria.